Production Potential and Some Agronomic Practices of Bambara Groundnut (Vigna subterrenea L). Verdc) Under Rainfed Conditions of South Gedarif Area (University of Khartoum Journal of Agricultural Sciences, 2023)
Field experiments were executed for two successive seasons(2009 and 2010), at the southern area of Gedarif State with the objectiveof studying the influence of sowing date and population density on theproductivity of a land race Bambara groundnut. Four sowing dates, viz.,27th of June, 9th, 19th and 27th of July and five combinations of inter-row*intra-row spacings, 40cmx30cm, 40x20, 30x30, 30x20 and 20x20,were used during both seasons. The data recorded in both seasons wereplant height, canopy width, 100 seed weight, shelling % and pod yieldton/ha. Results revealed highly significant differences in most ofmeasured parameters with respect to sowing date. Early sowing resultedin a significantly higher pod yield (4.3 ton/ha) when compared to latesowings (i.e. 2.3, 1.3 and 0.94 ton/ha for 9th, 19th and 27th of July,respectively). Variable plant spacing significantly affected pod yieldduring the first season, while no significant variation was observed duringthe second season. Nevertheless, higher yields were obtained with widerspacings. Accordingly, the early sowing from late June to early July issuggested as optimum sowing date for Bambara groundnut with row-cropspacings of 40-30cm inter-row and 30-20cm intra-row for the rain fedconditions of south Gedarif area.
Keywords: Bambara groundnut; sowing date; , population density